Investigation on tribological properties on strontium modified piston alloy under lubricated condition - Haque, Md. Mohafizul; Amir, Adibah; Ismail, Ahmad Faris (2009)
Research in tribological areas such as wear and friction has technological and economical significance since they change the shape of the work piece, tool and die interfaces. Thus, they affect the process, size and quality of the parts produced. The magnitude of tribological problem is evident in the countless parts and components that continually have to be repaired or replaced. In the present study, the tribological properties of Al-Si (LM-6 type) alloy have been carried out. The results show that in general, the increase in wear with an increase in input weight, rotational speed and sliding distance up to certain level of the alloy. Then the wear declined for as-cast and heattreated specimens under both modified and unmodified conditions. The volume of material worn was inversely proportional to the hardness of the alloy and thus, the heat treated alloy responded better than the normal cast alloy. During sliding, measurable debris transfer could be occurred, resulting weight gain of the sliding specimen. However, due to modification, wear of the alloy is minimized, and when it is heat treated, the material loss becomes zero.